Evaluation of the physical characteristics of Beta vulgaris and Intsia bijuga aqueous and methanolic extracts in comparison to haematoxylin stain / Nuraishah Mohamad, Fatimah Salim and Mohd Nazri Abu - Mohamad, Nuraishah; Salim, Fatimah; Abu, Mohd Nazri (Faculty of Health Sciences, Universiti Teknologi MARA, 2023)
The haematoxylin stain is universally recognised as pathology's gold-standard nuclear staining. This study evaluated and compared the pH value, and colour concentration of Intsia bijuga and Beta vulgaris extracts to that of haematoxylin. After lyophilisation, the plant material was extracted using methanol and water. Analyses were performed on the extracts' physical colour, pH, and colour concentration, and the results were compared to haematoxylin. A pH meter was used to obtain the pH value and spectrophotometric absorbance readings were taken to determine the colour concentration. The pH range for extracts of B. vulgaris was between 4.18 and 5.80, whereas the pH range for extracts of I. bijuga was between 4.46 and 4.65. There are statistically significant discrepancies (p < 0.001) in the pH and colour concentration analyses, as shown by the colour concentration statistical analysis. The colour properties of I. bijuga and B. vulgaris were also discussed to further enrich the understanding of their physical characteristics. In conclusion, the pH levels of the extracts were greater than those of haematoxylin. Regarding the colour concentration, the methanolic extract of B. vulgaris had a lower concentration than haematoxylin, while the other extracts had more significant concentrations than haematoxylin. In conclusion, the methanolic extract of I. bijuga shows the most significant similarity to haematoxylin in terms of its physical qualities.